Fenomena Vulkanisme Bawah Laut dalam Kajian Hadis dan Geologi - Mardiatus Solehah; Syamsul Arifin (El Nubuwwah Jurnal Studi Hadis, 2025)
Submarine volcanism plays a crucial role in shaping the Earth’s crust, yet its relevance within Islamic theological and hadith studies remains underexplored. This study addresses the problem of how underwater volcanic activity—although not explicitly mentioned in classical Islamic texts—may be meaningfully interpreted in relation to prophetic traditions that refer to major geological transformations, particularly within an eschatological framework. Employing a qualitative literature review method, this research analyzes contemporary volcanological and geoscientific findings on submarine volcanism, hydrothermal vents, and seafloor spreading, and juxtaposes them with selected hadiths describing fire emerging from the sea, large-scale terrestrial upheavals, and apocalyptic signs. The findings indicate that while hadith narratives employ symbolic and theologically nuanced language, several descriptions demonstrate conceptual coherence with modern scientific explanations of Earth’s internal dynamics. This coherence suggests that Islamic texts contain metaphorical indications of natural phenomena that have only been empirically understood through recent scientific advancements. The study further reveals that classical and modern Islamic scholarship provides an interpretive framework that accommodates scientific inquiry without reducing revelatory texts to purely empirical claims. The conclusion emphasizes that integrating modern geoscience with contextual and critical hadith interpretation enriches both scientific understanding and religious reflection. Such an interdisciplinary approach not only contributes to academic discourse on science–religion integration but also fosters environmental awareness and spiritual consciousness by framing natural phenomena as signs of divine order, rather than isolated physical events.